Q: X3 plus x2 plus 4x plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

(x + 4) / (x3 - 11x + 20) = (x + 4) / (x2 + 4x - 5)(x + 4) = 1 / (x2 + 4x - 5) = 1 / (x + 5)(x - 1), where x ≠ -4

Dividend: 4x4-x3+17x2+11x+4 Divisor: 4x+3 Quotient: x3-x2+5x-1 Remainder: 7

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

x3 - 10x2 + 24x = x(x2 - 10x + 24) = x(x2 - 4x - 6x + 24) = x[ x(x - 4) - 6(x - 4) ] = x(x - 6)(x - 4)

Related questions

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x(x + 4)(x - 4) or x3 - 16x

(x + 4) / (x3 - 11x + 20) = (x + 4) / (x2 + 4x - 5)(x + 4) = 1 / (x2 + 4x - 5) = 1 / (x + 5)(x - 1), where x ≠ -4

64 is the cube of 4 so: x3 + 64 = (x + 4)(x2 - 4x + 16)

x3 + 3x2 - 4x -12 x2(x + 3) - 4(x + 3) (x2 - 4)(x+3)

Dividend: 4x4-x3+17x2+11x+4 Divisor: 4x+3 Quotient: x3-x2+5x-1 Remainder: 7

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

x3 + 6x2 - 4x - 24 = (x + 6)(x2 - 4) = (x + 6)(x + 2)(x - 2)

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

Dividend: 4x^4 -x^2 +17x^2 +11x +4 Divisor: 4x +3 Quotient: x^3 -x^2 +5x -1 Remainder: 7

x3 - 3x2 + 4 Since the coefficients of the odd powers of x (=1) is the same as the sum of the even powers (-3+4=1), then x = -1 must be a root. That is to say, (x + 1) is a factor. So you can rewrite the expression as x3 + x2 - 4x2 - 4x + 4x + 4 = x2(x + 1) - 4(x + 1) + 4(x + 1) = (x + 1)*(x2 - 4x + 4) = (x + 1)*(x - 2)2